From lurkers to networkers: Cultural and epistemic dimensions of developing professional learning networks in online graduate education - Dennen, Vanessa (Proceedings of the International Conference on Networked Learning, 2026)
Professional learning networks (PLNs) are topically-focused networks comprised of people, spaces, and tools. They offer an opportunity for professional growth and lifelong learning by fostering ongoing connections that offer resources and interactions. They are inherently unique to each individual, and their development is an ongoing and iterative process. While PLNs are often developed organically by professionals, the concept can be taught to students to prepare them for ongoing learning within their eventual careers. This study explores how graduate students in an online course experience the development of professional learning networks (PLNs) through cultural and epistemic lenses. Students were asked to engage in PLN development on the topic of their choice, whether personal or professional. There were no requirements for the PLN or the extent of its development. Drawing on student reflections about their PLN-building process, the study employs two theoretical frames. First, a cultural network perspective is used to examine the interplay of the individual, their network, and culture. Second, to gain an epistemic perspective, the Networked Knowledge Activities (NKA) framework is used to consider how students engage with knowledge within their developing PLNs. Findings show that PLN development focused on finding relevant resources and identifying and joining pre-existing groups. Additionally, connections to prominent thought leaders on social media platforms occurred. The course space served as a model for engaging in networked knowledge activities, some of which students deployed in their developing PLNs. Of the NKAs, collecting and curating were the entry behaviors, providing immediate content rewards and offering a way to learn about group and space norms. From there, sharing and brokering were likely to occur once individuals began to feel more comfortable. Some students ventured into negotiating knowledge, while few created and shared unique knowledge objects, although more indicated plans to do so in the future. This progression of activities shows the evolution toward more intentional engagement in a professional networked learning setting. Findings show that PLN development is shaped by both internal motivations and external cultural forces. Students made deliberate choices about where to engage, which communities to join, and how to manage their digital identities. Epistemically, they grappled with questions of knowledge legitimacy, relevance, and organization, often developing strategies to manage information overload and align their networks with their learning goals. Overall, the findings suggest that PLN development is not simply a networking task, but requires cultural and epistemic support to facilitate a shift from observation to contribution in professionally consequential online spaces